Interventions for pre‐school children in foster care: A systematic review of randomised controlled trials of child‐related outcomes - Natalie Kirby; Camilla Biggs; Megan Garside; Gloria Cheung; Philip Wilson; Matt Forde; Manuela Deidda; Dennis Ougrin; Fiona Turner; Karen Crawford; Helen Minnis (JCPP Advances)
Abstract Background Children in foster care are at high risk of future mental health and developmental difficulties. A number of interventions may be helpful; however, the effectiveness of interventions specifically for pre‐school children in foster care is not well established. This is an important omission, since infancy and early childhood may be the optimal period for interventions to prevent future problems. The current systematic review set out to establish the existing evidence base for interventions to improve social‐emotional, developmental and relational outcomes for pre‐school children in foster and kinship care. Methods Searches of online databases were undertaken in June 2023 with keyword search terms related to the study population and design. Studies utilising a randomised control design to measure the effectiveness of interventions for foster children aged 0–7 years were included. The methodological quality of included studies was assessed using the Cochrane Risk of Bias (ROB‐2) tool and effects evaluated using narrative synthesis and GRADE assessments of included interventions and outcomes. Results Searches identified 6815 results. Twenty studies, describing seven interventions, met inclusion criteria. Fifteen studies reported intervention benefits comparative to control in at least one outcome domain, with particularly good evidence for Attachment and Behaviour Catch‐Up (ABC) in improving developmental outcomes. There was also evidence for Multi‐Treatment Foster Care for Pre‐Schoolers (MTFC‐P), Kids In Transition To School (KITS), Parent‐Child Interaction Therapy (PCIT) and HeadStart in improving behavioural outcomes. The findings for relational outcomes, including attachment, were mixed; however, there was some evidence for MTFC‐P and ABC in reducing avoidant attachment. Conclusions This systematic review contributes to our current understanding of how we might best support pre‐school children in foster care. It remains unclear whether the effectiveness of particular interventions may be moderated by participant or intervention characteristics. Further research is needed to understand which interventions work best for whom in this group. Despite some variability in methodological quality and heterogeneity across studies, our findings suggest that certain interventions are likely to be helpful for young children in foster care. Dissemination and ongoing evaluation of the evidence‐based interventions highlighted within this review should be implemented in clinical practice.